Impact of COVID-19 on CT-diagnosed acute appendicitis and diverticulitis: was there collateral damage?. Issue 7 (July 2022) - Kilcoyne, A.; Goiffon, R.J.; Anderson, M.A.; Cahalane, A.M.; O'Shea, A.; Balthazar, P.; Yeung, T.; Jang, S.; Som, A.; Qadan, M.; Lee, S.I.
Abstract : AIM: To evaluate the change in diagnosis rates, disease severity at presentation, and treatment of acute appendicitis and diverticulitis during the COVID-19 shutdown. MATERIALS AND METHODS: Following institutional review board approval, 6, 002 CT examinations performed at five hospitals for suspected acute appendicitis and/or diverticulitis over the 12 weeks preceding and following the shutdown were reviewed retrospectively. Semi-automated language analysis (SALA) of the report classified 3, 676 CT examinations as negative. Images of the remaining 2, 326 CT examinations were reviewed manually and classified as positive or negative. Positive cases were graded as non-perforated; perforated, contained; and perforated, free. RESULTS: CT examinations performed for suspected appendicitis and/or diverticulitis decreased from 3, 558 to 2, 200 following the shutdown. The rates of positive diagnoses before and after shutdown were 4% (144) and 4% (100) for appendicitis and 8% (284) and 7% (159) for diverticulitis ( p> 0.2 for both). For positive CT examinations, the rates of perforation, hospitalisation, surgery, and catheter drainage changed by –2%, –3%, –2%, and –3% for appendicitis ( n= 244, p> 0.3 for all) and +6% ( p= 0.2) +9% ( p= 0.06), +4% ( p= 0.01) and +1% ( p= 0.6) for diverticulitis ( n= 443). CONCLUSION: CT examinations performed for suspected appendicitis or diverticulitis declined after the shutdown, likely reflecting patients leaving urban centres and altered triage of non-COVID-19 patients. The diagnosis rates, disease severity at presentation, and treatment approach otherwise remained mostly unchanged. Highlights: CTs for suspected appendicitis or diverticulitis declined following the shutdown. Decrease in CT volume likely reflected patients leaving urban centers. Diagnosis rates, disease severity at presentation, and treatment approach were mostly unchanged.